Effectiveness and cost-effectiveness of an intensive and abbreviated individualized smoking cessation program delivered by pharmacists: A pragmatic, mixed-method, randomized trial. (November 2022) - Phillips, Leslie C.E.; Nguyen, Hai; Genge, Terri L.; Maddigan, W. Joy
Background: Tobacco use is the leading preventable cause of morbidity and mortality in Canada. Smoking cessation programs (SCPs) that are effective, cost-effective and widely available are needed to help smokers quit. Pharmacists are uniquely positioned to provide such services. This study compares the abstinence rates between 2 pharmacist-led SCPs and the cost-effectiveness between these and a comparator group. The study was conducted in St. John's, Newfoundland and Labrador. Methods: This pragmatic, mixed-method trial randomized smokers to either an existing intensive SCP or a new abbreviated SCP designed for community pharmacies. The primary outcome was 6-month abstinence rates. Cost-effectiveness was determined using abstinence rates for the SCPs and a comparator group. Incremental costs per additional quit were calculated for the trial duration, and incremental costs per life-year gained were estimated over a lifetime. Results: Quit rates for the SCPs were 36% (intensive) and 22% (abbreviated) ( p = 0.199). Incremental costs per life-year gained for the SCPs were 1576 (intensive) and 1836 (abbreviated). The incremental costs per additional quit, relative to the comparator group, for the SCPs were 1217 (intensive) and 1420 (abbreviated). Discussion: Both SCPs helped smokers quit, and quit rates exceeded those reported for a comparator group that included a general population of adult smokers ( 7%). The incremental costs per additional quit for both SCPs compare favourably to those reported for other initiatives such as quit lines and hospital-based interventions. Conclusion: Pharmacist-led smoking cessation programs are effective and highly cost-effective. Widespread implementation, facilitated by remuneration, has potential to lower smoking prevalence and associated costs and harms.